Geometries of the Living - Alain Prochiantz (Collège de France, 2016)
My idea of a theory in biology is quite different from the theoretical biology that is expressed as equations of observed or photographed phenomena. I have a simpler, more concrete conception. Not a mathematical description of what is seen, but an evolving model, a tool developed through bricolage, with mathematics perhaps, but also natural language: one that serves above all to understand the unseen; to guess, beneath the visible, the invisible dimensions of life forms, the underlying "logic".